Production of high purity silica by microfluidic-inclusion fracture using microwave pre-treatment. (15th January 2019) - Buttress, A.J.; Rodriguez, J.M.; Ure, A.; Ferrari, R.S.; Dodds, C.; Kingman, S.W.
Highlights: Upgrading quartz powder enhanced with microwave pretreatment. Microwave heating of fluidic inclusions causes their explosive decrepitation. Total contaminants have been reduced from 158 ± 22 ppm to 30 ± 3 ppm. Abstract: Demand for high purity silica used in component manufacture is set to outstrip current supply in the near future. As such, alternative processing routes to feed-stock materials suitable for use in lighting and solar cell fabrication are required, without having to rely on reject material from semi-conductor manufacture. In this work, we report a facile, environmentally friendly method of producing quartz powder with a total residual impurity level of 30 ± 3 ppm from whole pebbles having an initial impurity level of 158 ± 22 ppm. This has been achieved using a metallurgical upgrading process incorporating microwave pre-treatment, crushing and milling, High Intensity Wet Magnetic Separation (HIWMS) and acid leaching. This process yielded a quartz powder having an 80% reduction in residual impurities compared to the untreated quartz pebbles. Pre-treatment of whole quartz pebbles in a multimode microwave cavity for 10 min yielded a reduction of the residual elemental impurity content associated with micro-fluidic inclusion sites containing calcium, potassium and sodium of 84, 78, and 50% respectively. Statistically significant reduction in residual aluminium phases was also observed (83%) compared to the as received material to below the IOTA® specification for Ultra High Pure Quartz produced by Sibleco. Mechanistically, this has been achieved by selectively heating impurity containing micro-fluidic inclusion sites. Resulting in their explosive decrepitation and enabling removal of the impurities in subsequent processing steps. It has been concluded that natural quartz pebbles can be upgraded through a combination of microwave treatment, magnetic and chemical refinement to produce a viable feedstock for the subsequent production of solar grade silicon.